2014
DOI: 10.1186/1756-0500-7-473
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of hospital stay and mortality in dengue virus infection-experience from Aga Khan University Hospital Pakistan

Abstract: BackgroundDengue virus infection (DVI) is very common infection. There is scarcity of data on factor associated with increased hospital stay and mortality in dengue virus infection (DVI). This study was done to know about factors associated with increased hospital stay and mortality in patients admitted with DVI.ResultsOut of 532 patients, two third (72.6%) had stay ≤3 days while one third (27.4%) had stay greater than 3 days. The mean length of hospital stay was 3.46 ± 3.45 days. Factors associated with incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
51
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 15 publications
12
51
0
1
Order By: Relevance
“…There is evidence from available literature showing an association between mortality and various clinical, biochemical and haematological parameters like haematocrit, prothrombin time, activated partial thromboplastin time, lactate levels, acute kidney injury and ARDS. [6][7][8][9] In our study, there was no relation of mortality with gender of the patients. Males constituted 64% of the 14 deaths (p value = 0.534).…”
Section: -35mentioning
confidence: 82%
See 2 more Smart Citations
“…There is evidence from available literature showing an association between mortality and various clinical, biochemical and haematological parameters like haematocrit, prothrombin time, activated partial thromboplastin time, lactate levels, acute kidney injury and ARDS. [6][7][8][9] In our study, there was no relation of mortality with gender of the patients. Males constituted 64% of the 14 deaths (p value = 0.534).…”
Section: -35mentioning
confidence: 82%
“…Similar results were observed by Khalil et al, in their study conducted in Pakistan and other studies. 8,23,24 The presence of altered sensorium and abnormal reflexes is indicative of CNS involvement in the form of encephalopathy. As evidenced in this study and suggested in several other studies, brain involvement is associated with a higher incidence of mortality in dengue patients (p value <0.001).…”
Section: -35mentioning
confidence: 99%
See 1 more Smart Citation
“…Old age, acute renal failure, acute respiratory failure, acute hepatitis, DSS/DHF, altered mental status, bleeding, and coagulopathy have been reported to be predictive factors for fatality in the patients with DF [1921]. In addition, hypoalbuminemia and high serum lactate level have been associated with high mortality [38].…”
Section: Discussionmentioning
confidence: 99%
“…Various predictive factors for mortality have been identified in DF, including old age, acute renal injury, acute respiratory failure, hepatitis, altered mental status, bleeding and coagulopathy [1921]. The acute physiology and chronic health evaluation (APACHE) II score may predict mortality in patients admitted to an intensive care unit (ICU) in a prospective observational cohort study [22].…”
Section: Introductionmentioning
confidence: 99%